Two colistin resistance-producing Aeromonas strains, isolated from coastal waters in Zhejiang, China: characteristics, multi-drug resistance and pathogenicity - Chen, Hong-Xian; Chen, Fang-Jie; Zhou, Qian-Jin; Shang, Shi-Lin; Tang, Biao; Xu, Zhong-Jie; Duan, Li-Jun; Jin, Jing-Lei; Xu, Gui-Zong; Yan, Mao-Cang; Chen, Jiong (Frontiers in Microbiology, 2024)
Aeromonas spp. are ubiquitous inhabitants of ecosystems, and many species are opportunistically pathogenic to humans and animals. Multidrug-resistant (MDR) Aeromonas species have been widely detected in hospitals, urban rivers, livestock, and aquatic animals. In this study, we identified two Aeromonas isolates, namely A. veronii 0728Q8Av and A. caviae 1029Y16Ac, from coastal waters in Zhejiang, China. Both isolates exhibited typical biochemical characteristics and conferred MDR to 11 kinds of antibiotics, remaining susceptible to ceftazidime. Whole-genome sequencing revealed that both isolates harbored multiple antibiotic resistance genes (ARGs) and several mobile genetic elements (MGEs) on the chromosomes, each containing a resistance genomic island (GI), a typical class 1 integron, a transposon, and various insertion sequences (ISs). Most ARGs were situated within the multiple resistance GI, which contained a class 1 integron and a transposon in both Aeromonas isolates. Furthermore, a chromosomal mcr-3.16 gene was identified in A. veronii 0728Q8Av, while a chromosomal mcr-3.3 was found in A. caviae 1029Y16Ac. Both mcr-3 variants were not located within but were distanced from the multidrug resistance GI on the chromosome, flanking by multiple ISs. In addition, a mcr-3-like was found adjacent to mcr-3.16 to form a tandem mcr-3.16-mcr-3-like-dgkA structure; yet, Escherichia coli carrying the recombinants of mcr-3-like did not exhibit resistance to colistin. And an incomplete mcr-3-like was found adjacent to mcr-3.3 in A. caviae 1029Y16Ac, suggesting the possibility that mcr-3 variants originated from Aeromonas species. In vivo bacterial pathogenicity test indicated that A. veronii 0728Q8Av exhibited moderate pathogenicity towards infected ayu, while A. caviae 1029Y16Ac was non-virulent. Thus, both Aeromonas species deserve further attention regarding their antimicrobial resistance and pathogenicity.